The Effect of Audio-Visual Podcast Media on Students’ Ability to Identify Cause-and-Effect Conflicts in Narrative Texts - -, Nursadila; -, Rasdawita; Bambang, Siti Enik Mukhoiyaroh (Jurnal Bahasa Indonesia Prima (BIP), 2026)
This study aims to determine the effect of using audio-visual podcast media on students’ ability to identify cause-and-effect conflicts in narrative texts among Phase F students at SMA Negeri 10 Jambi City. This research employed a quantitative approach with a quasi-experimental design using a pre-test and post-test control group. The subjects consisted of 72 students divided into an experimental class and a control class. Data were collected through tests administered before and after the treatment. The results showed that the use of audio-visual podcast media had a better effect compared to conventional learning methods. Students who used audio-visual podcast media demonstrated a higher improvement in identifying cause-and-effect conflicts in narrative texts. Therefore, it can be concluded that audio-visual podcast media is effective in teaching narrative texts, as it helps students understand the sequence of events more systematically and increases their engagement in the learning process.